Determinación de la calidad del agua mediante la comunidad de macroinvertebrados acuáticos en el río Mosca del cantón Junín - Cruz Lara, Jessica Nicol (2022)
The objective of the research was to determine the quality of the Mosca River in Junín canton through the presence of aquatic macroinvertebrate communities. For this, six sampling stations were established along the river, later the macroinvertebrates were collected with the help of the surber and kick nets, the Shannon-Weaver, BMWP and EPT indices were used to establish the diversity and tolerance to contamination of aquatic macroinvertebrates, in addition, the physicochemical parameters that were measured were: pH, temperature and dissolved oxygen. The macroinvertebrates collected in the sampling stations amount to 1038 individuals, of which 627 were collected in the dry season and 411 in the rainy season. 20 families were identified; the orders with the highest abundance of specimens are the Ephemeroptera with 241 individuals corresponding to the leptophlebiida family. The results of the investigation were that through the Shannon-Weaver index, the water quality of the Mosca River was clean water, with a high diversity of species, in addition, the EPT index showed that the quality of the water in the Mosca River is Good, it was also determined that the correlation between the chemical physical parameters and the EPT index in the dry season is inverse in the parameters Temperature (-0.17) and pH (-0.76) and the EPT index, because the pearson’s coefficient ranges from -1 to 0, and in the rainy season, an indirect correlation was obtained, where the Pearson’s coefficient of dissolved oxygen is -0.40, the temperature obtained -0.20 and the pH -0.26.